Where's my Easter egg? - Ziefert, Harriet; Brown, Richard Eric, 1946- (New York, N.Y. : Puffin Books, 1985)
Nicky the cat hunts for his Easter egg in the sandbox, the hen house, and other places hidden by movable flaps, where he finds many kinds of eggs.
1.9
K-3
Keywords: Toy and movable books -- Specimens; Toy and movable books; Easter eggs -- Fiction; Cats -- Fiction; Eggs -- Fiction; Toy and movable books; Easter -- Fiction; Cats -- Fiction; Eggs -- Fiction